Survey Study Assessing Attitudes and Experiences of Pediatric Registered Dietitians Regarding Blended Food by Gastrostomy Tube Feeding. (June 2015) - Johnson, Teresa W.; Spurlock, Amy; Pierce, Leah
Background: Families of children requiring nutrition support may be interested in providing blenderized food by gastrostomy tube (BFGT). Some registered dietitians (RDs) recommend partial or full BFGT for children with tube feeding intolerance who are unresponsive to standard interventions. There is little published information on the safety and efficacy of BFGT feeding. The purpose of this survey was to elicit experiences of pediatric RDs with BFGT in clinical practices. Methods: A survey instrument was distributed to members of the Pediatric Nutrition Practice Group to report experiences of BFGT in clinical practice. Results: Response rate was 9.9% of total members (N = 2, 448). Over half (58%) of the 244 respondents use and recommend BFGT. Reasons for use included parent request (70.2%), tube feeding intolerance (22.9%), and inability to obtain commercial formula (6.1%). Seventy-nine percent reported an overall positive outcome with BFGT. Older RDs were more familiar with BFGT but less likely to use it compared with younger RDs who use BFGT or wanted more information ( P = .007). Twelve percent did not use or recommend BFGT due to concerns about bacterial contamination, unknown nutrient composition, inability to provide follow-up, and/or facility policy violations. Twenty-eight percent were familiar with BFGT but wanted more information. Conclusions: Interest in BFGT is largely parent-driven or explored as an option for children with tube feeding intolerance. Almost 80% of RDs using this feeding substrate report overall positive outcomes, but 28% indicate they want more information on using BFGT in clinical practice.